Bevacizumab plus chemotherapy in metastatic colorectal cancer patients treated in clinical practice. (September 2012) - Rossi, Luigi; Veltri, Enzo; Zullo, Angelo; Zoratto, Federica; Colonna, Maria; Di Seri, Marisa; Longo, Flavia; Mottolese, Marcella; Giannarelli, Diana; Ruco, Luigi; Romiti, Adriana; Barucca, Viola; et al.
Aim: The effect of KRAS status on response to bevacizumab plus chemotherapy in metastatic colorectal cancer is still unclear. We aimed to evaluate the overall clinical response to such a therapy in clinical practice and assess the role of KRAS status on therapy response.Patients & methods: This was a retrospective study enrolling 108 metastatic colorectal cancer patients. KRAS mutation analysis was performed by PCR.Results: Overall, 41.7% of patients had stable disease, 39.8% a partial response, 3.7% a complete response and 14.8% disease progression. Both clinical benefit and objective response rate tended to be higher in patients with only hepatic metastases than those with extrahepatic or multiple metastases. Response to therapy would appear to be independent of KRAS status, but larger studies are needed.Conclusion: Bevacizumab plus chemotherapy provides clinical benefit and objective response rate in patients with metastatic colorectal cancer independently of KRAS expression, especially in those patients with only liver metastases.